Family Planning Commodity Financing And Supply Chain In Uganda - HEPS (HEPS, 2021)
Uganda was represented at the 2012 London Family Planning (FP) Summit at the highest political level by President Yoweri Museveni who pledged to ensure an enabling policy environment to allow women to exercise their FP choices, to increase the country’s financial investment in FP, and to strengthen service delivery. Government of Uganda (GOU) pledged to increase its annual budget allocation for FP supplies from USD 3.3 million (FY 2012) to USD 5 million for the next five years and to mobilize an additional USD 5 million annually from donors. This would be supported by the development of a reproductive health (RH) sub-account to track RH resource flows. During the 2017 London FP Summit, GOU renewed its FP2020 commitments, but this time around the it pledged to raise an additional USD 20 million annually from Health Development Partners (HDPs) to top up on to the USD 5 million annually from the domestic budget. A substantial number of clients access FP commodities from the private sector through out-of-pocket payments. Out-of-pocket payments expose the population to catastrophic and impoverishing health expenditures, increasing socioeconomic inequality, thereby undermining progress towards Universal Health Coverage (UHC). The national health insurance scheme (NHIS), which would have cushioned people against such risks, has dragged and existing schemes do not cover FP. FP commodities for use in the public sector are included in the Uganda Clinical Guidelines (UCG) and the Essential Medicines and Health Supplies (EMHS) List of Uganda. These commodities also must be registered by the National Drug Authority (NDA). The Ministry of Health’s National RMNCAH Quantification Report guides GOU and partners on the quantities of commodities required and when to procure them. Guided by the Supply Plans in the quantification report, GOU and Health Development Partners (HDPs) make financial commitments andand initiate the procurements of the commodities.The main funders of FP commodities include GOU, UNFPA, USAID and the Global Fund. GOU funding consists of direct allocations from the national budget and grants and loans from HDPs. The commodities are then cleared through customs and warehoused at National Medical Stores (NMS) for the public sector and Joint Medical Store (JMS) for private-not-for-profit (PNFP) sector. In spite of the increased financial allocation by GOU and HDPs to FP commodities, major gaps in financing and access to contraceptives continue to persist in Uganda. The financial need for FP for FY2020/21 is estimated at USD 32.93 million, of which GOU’s contribution from domestic resources is estimated at USD 4.21 million, leaving a funding gap of USD 28.72 million to be filled by HDPs, grants and loans. It is important to note that out of the domestic finances invested in FP commodities,98% of these investments have been used to procure mama kits. Additionally, in 2020, World Bank donated USD 15 million (UGX 57 billion) from its maternal child health project to the COVID-19 national response. Part of these funds had been intended for sexual and reproductive health (SRH) essential medicines and commodities, including FP commodities.